Tracked Changes. Optical fibre cables. Generic specification. Basic optical cable test procedures. Electrical test methods. Lightning test (for OPGW, OPPC and OPAC), Method H2 Part 1-402, (24th November 2021) - British Standards Institution,
No abstract available